A new approach to the assessment of cognition in drivers: Applying the multiple errands test for use in a simple parking exercise. (February 2015) - Lanceley, Sarah
Statement of context: The assessment of fitness to drive can often involve cognitive screening carried out by an occupational therapist. In the field of driving assessment there is a challenge to select and administer suitable office-based cognitive tests, in conjunction with an on-road assessment, which can be used to provide supporting evidence of a client's fitness to drive.Critical reflection on practice: This practice analysis aims to reflect on the inherent problems of office-based testing.Implications for practice: The author describes the development of a cognitive test based on the Multiple Errands Test - Hospital Version, which can be used while driving in a real-life situation.